Vallisneria spiralis L. (Hydrocharitaceae) in Lakes in the Vicinity of Konin (Kujawy Lakeland) - Hutorowicz, Andrzej (Biodiversity: Research and Conservation, 2006)
In the last eleven years Vallisneria spiralis L. colonized three lakes situated in the Kujawy Lakeland, i.e. Lake Licheńskie, Lake Wąsosko-Mikorzyńskie and Lake Pątnowskie, which in 1958 were included in the open cooling system of heat and power stations. The aim of the studies conducted in 2004 was to determine the seasonal dynamics of this species as dependent upon thermal variations. Phenological observations, temperature measurements, and examinations of changes in the spatial structure of V. spiralis communities at selected localities were performed from the end of April to the end of October. A correlation was observed between the life-cycle of V. spiralis and water temperature. V. spiralis was also found to be tolerant of a short photoperiod. Apart from great vegetative reproduction ability, these were the main factors that decided about the biogeographical success of this species.